From Education to Enterprise: Redefining Entrepreneurship Education to Enhance Venture Creation in Rwanda’s Private Higher Learning Institutions - (:unkn) unknown (My University, 2025)
This study investigates the complex relationship between entrepreneurship education (EE) and venture creation among graduates of private higher learning institutions in Rwanda. While EE has been widely promoted as a solution to graduate unemployment and economic diversification, its real-world impact on startup formation remains contested. Through a theory-driven meta-synthesis of secondary data, this paper evaluates the long-term effectiveness of EE using four analytical lenses: Human Capital Theory, the Theory of Planned Behavior, Entrepreneurial Ecosystem Theory, and Experiential Learning Theory. Findings reveal that while EE significantly boosts entrepreneurial intentions through cognitive, affective, and attitudinal development, the actual transition to sustainable venture creation is severely constrained. Statistical evidence shows that measured entrepreneurial skills explain less than 1.2% of variance in startup intention, and only 3% of graduates launch formal ventures within two years post-graduation. Ecosystem bottlenecks—including limited access to finance, fragmented mentorship systems, weak incubation support, and constrained market linkages—undermine the EE-to-enterprise pathway. Comparative analysis with other developing economies confirms Rwanda’s unique asymmetry: a strong policy-level commitment to EE exists without the institutional infrastructure to translate intent into execution. The study recommends embedding experiential learning components—such as mentorship, internships, and startup competitions—into EE curricula, while simultaneously strengthening national innovation systems and funding pathways for graduate entrepreneurs. This paper contributes a rare, context-specific synthesis that bridges theoretical insight with empirical critique, offering policy and institutional recommendations to realign EE with Rwanda’s economic ambitions. It highlights the need for ecosystem-sensitive reforms to ensure that entrepreneur
Keywords: African Research